Study of the Influence of Credit Giving at PT. BPR Cita Dewi Karanganyar - Evita Kusuma; Arif Nugroho Rachman (Journal of Business, Management, & Accounting, 2022)
The purpose of this study is to determine the internal control system, capacity, credit quality, and loan interest rates have an influence on credit giving at PT BPR Cita Dewi Karanganyar. By using primary data, obtained using quantitative statistical methods and data collection techniques using questionnaires. The total sample used in this study was 37 respondents using the saturated sampling method. This study uses multiple linear regression analysis to explain that the internal control system, capacity, and credit quality have a significant positive effect on credit giving, but loan interest rates do not affect credit giving.